(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the history of the use of language training exercises and the basics of giving it in textbooks of English language textbooks. The problems which may occur when teaching English with the help of old methods are illuminated. Factors of applying linguocultural exercises, which are important in preparing learners to communication, are listed.